Multi-objective model-based design optimization of hydraulic shock absorbers - Wszołek, Grzegorz (Computer Assisted Methods in Engineering and Science, 2016)
This paper presents the multi-objective optimization process of a hydraulic damper design based on its interdisciplinary meta-model considering both the properties of a damper and of the testing equipment used for the purpose of design criteria verification, and in particular the tolerance band criterion of damping force characteristics, the criterion of maximum permissible vibration level expressed with the piston rod acceleration and the criterion of fatigue durability for the damper’s hydraulic valve system. The meta-model of a damper and a testing bench include the following models: mechanical model, hydraulic model, electro-hydraulic model and valve system fatigue durability model. The multi-objective optimization method provides an optimal solution by means of Pareto frontier. Furthermore, all potential feasible solutions are ranked according to additional customer preferences to select the most suitable ones. The proposed method is intended to be used to determine the best starting point in a new shock absorber design process.